Usable thoughts : climate, water and weather in the twenty-first century - Glantz, Michael H.; Ye, Qian. (Tokyo, Japan ; New York : United Nations University Press, 2010)
Drawing upon a series of quotations taken from the World Meteorological Organization-sponsored publication, "Climate: Into the 21st Century," the authors of this publication set out to encourage thought and discussion on the earth's climate system, including its interrelatedness to human society and the environment, the impact of climate variability, and climate extremes and change.--Publisher's description
Energy and societyThe earth's freshwater resources; Seeking answers on climate change; 5 The Century Ahead; Immediate challenges; Adapting to future change; Protecting the planet and its people; Future surprises?; Concluding Thoughts; The Limits to Growth and The Kyoto Protocol: The need for"tipping point" assessments; Selected Reading
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Climatology; Climatic changes -- Effect of human beings on; Weather forecasting; Climatology -- Popular works; Climatic changes -- Effect of human beings on -- Popular works; Weather forecasting -- Popular works; Climat -- Ouvrages de vulgarisation; Climat -- Changements -- Effets des êtres humains sur -- Ouvrages de vulgarisation; Temps (Météorologie) -- Prévision -- Ouvrages de vulgarisation; Climat -- Changements -- Effets des êtres humains sur; Temps (Météorologie) -- Prévision.; SOCIAL SCIENCE -- Human Geography; Climatic changes -- Effect of human beings on; Climatology; Weather forecasting; Popular works